Suistanable Electrical Energy Development In Solar Energy On Maritime Governance In Batam City - Deviance Ramadana Saragih; Muhammad Fazrullah; Sri Rejeki Asih Purba (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
The use of fossil energy in the maritime industry has become a major source of carbon emissions and vulnerability to fuel price fluctuations. In an effort to overcome these challenges and move towards a more sustainable future, the use of solar energy has emerged as a significant potential solution. Batam City, with its strategic location and rapidly growing maritime interests, has great potential to adopt solar energy in its maritime operations. This study aims to investigate the potential and challenges of developing solar-based sustainable electrical energy in the maritime sector in Batam City. We identify the most suitable locations for solar panel installations, explore efficient energy storage technologies, and analyze reliable maritime grid system integration. Additionally, we discuss personnel training and environmental awareness efforts necessary to support this transition. This study also reviews the role of policy and regulation in encouraging investment in solar energy and encouraging collaboration with relevant stakeholders. The research results show that the use of solar energy in maritime governance in Batam City can reduce carbon emissions, increase energy security and reduce operational costs in the long term. This study provides valuable insights for decision making and strategic planning for local governments, industry players and academic institutions interested in realizing sustainable and future-oriented maritime governance.